PATHOPHYSIOLOGY OF THE KIDNEYS AND KIDNEY DISEASES - Yusupova Maftuna Azamatovna (Ta’lim innovatsiyasi va integratsiyasi, 2025)
Abstract: The kidneys are vital organs responsible for maintaining homeostasis in the human body. They play a crucial role in blood filtration, waste excretion, electrolyte and fluid balance, acid-base regulation, and blood pressure control. Pathophysiological processes affecting the kidneys can lead to various diseases, including acute and chronic kidney failure, nephritis, nephrotic syndrome, kidney stones, and other disorders.